2023
DOI: 10.1007/s00415-022-11530-z
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glymphatic drainage underlying obstructive sleep apnea is associated with cognitive dysfunction

Abstract: Obstructive sleep apnea (OSA) is highly prevalent but easily undiagnosed and is an independent risk factor for cognitive impairment. However, it remains unclear how OSA is linked to cognitive impairment. In the present study, we found the correlation between morphological changes of perivascular spaces (PVSs) and cognitive impairment in OSA patients. Moreover, we developed a novel set of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) methods to evaluate the fluid dynamics of glymphatic drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…The relationship between sleep and PVS burden was explored in eight studies (Berezuk et al, 2015; Lysen et al, 2022; Piantino et al, 2021; Aribisala et al, 2023; Hicks et al, 2023; Soitgu et al, 2023; Wang et al, 2023; Shih et al, 2023), with all except one (Hicks et al, 2023) identifying an association between at least one metric of sleep and PVS burden. Berezuk et al, (2015) and Lysen et al, (2022) reported a negative correlation between both sleep efficiency and PVS burden.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between sleep and PVS burden was explored in eight studies (Berezuk et al, 2015; Lysen et al, 2022; Piantino et al, 2021; Aribisala et al, 2023; Hicks et al, 2023; Soitgu et al, 2023; Wang et al, 2023; Shih et al, 2023), with all except one (Hicks et al, 2023) identifying an association between at least one metric of sleep and PVS burden. Berezuk et al, (2015) and Lysen et al, (2022) reported a negative correlation between both sleep efficiency and PVS burden.…”
Section: Resultsmentioning
confidence: 99%
“…New diffusion tensor imaging studies using analysis along perivascular space (APLS) as measure of glymphatic functioning link both AH 102 and OSA 103 to glymphatic impairment. A recent study employing dynamic contrast enhanced MRI in OSA patients revealed enlarged perivascular spaces, lateral ventricles and disturbed glymphatic flow as well as cognitive deficits measured by MMST and MoCA 104 . After 1 month of CPAP glymphatic function of OSA patients improved, thus emphasizing the need of treating OSA as a risk factor for dementia/NCD.…”
Section: Discussionmentioning
confidence: 96%
“…The importance of glymphatic drainage was demonstrated by Wang et al [40]. They found enlarged perivascular spaces in the bilateral frontal cortex and basal ganglia in OSAHS patients and even more prominently so in the severely hypoxic OSAHS patients.…”
Section: Effect Of Positive Airway Pressure Treatment On the Glymphat...mentioning
confidence: 92%
“…Search term PubMed ("Mild cognitive impairment" OR "cognitive decline" OR "cognitive dysfunction" OR "mild cognitive deficit" OR "Alzheimer disease" OR AD OR amyloid OR "MCI" OR "amnestic mild cognitive impairment" OR "degenerative disease" OR "amyloid precursor protein A total of 45 studies were found. Of the 45, 15 studies discussed the hypothesised glymphatic system in relation to sleep [11,12,[23][24][25][26][27][28][29][30][31][32][33][34][35], 5 studies assessed the impact of PAP on brain fluid diffusivity in patients with OSAHS [36][37][38][39][40], 4 studies assessed the influence of PAP treatment on the level of AD biomarkers [29,31,41,42], 11 studies measured the impact of PAP treatment on cognitive function in OSAHS [1,4,14,[43][44][45][46][47][48][49][50] and 10 studies measured the impact of PAP treatment on cognitive function in OSAHS and aMCI/AD [7,8,17,20,21,[51][52][53][54]…”
Section: Databasementioning
confidence: 99%